PERAN KELUARGA DALAM MEMANDIRIKAN ANAK RETARDASI MENTAL DI YAYASAN PEMBINAAN ANAK CACAT MANADO TAHUN 2011 - Johana Tuegeh; Frenny Rompas; Djoni Ransun (POLTEKKES KEMENKES MANADO, 2012)
The family is the smallest unit of society is made up of heads of households as well as a few peoplethat get together and live in one roof in a state of interdependence. Each family member has a role toplay. The role of parents affects the child grows.The purpose of this study was Getting a picture of the